Memórias de uma Escola Isolada Rural: estudo de um Livro de Visitas (1928-1948) - Garnica, Antonio Vicente Marafioti [UNESP] (Centro de Estudos Educação e Sociedade (CEDES), 2011)
Cet article étudie le livre de visites de l'ancienne école mixte de la Fazenda Ponte Alta/Bela Vista, liée au groupe scolaire de la ville de Bariri, dans l'état de São Paulo (SP). À partir des registres de vingt ans d'activités (1928-1948), nous retraçons les exigences des inspecteurs primaires et si ces exigences provenaient (ou non) de professeurs et de la communauté paysanne pour ébaucher un cadre socio-historique de l'enseignement des premières lettres dans la zone rurale de l'intérieur de l'état de São Paulo. Il en résulte que le discours qui défendait l'égalité de chances pour les populations urbaines et rurales négligeait généralement le besoin de promouvoir l'égalité de conditions pour que la communauté rurale puisse profiter des chances qui lui étaient promises.

O artigo estuda o Livro de Visitas da antiga Escola Mista da Fazenda Ponte Alta/Bela Vista, vinculada ao Grupo Escolar da cidade de Bariri (SP). A partir dos registros de vinte anos de atividades (1928-1948), são consideradas as exigências dos inspetores de ensino e os modos como essas exigências eram (ou não) encaminhadas pelas professoras e pela comunidade campesina, com o que se esboça um cenário sócio-histórico sobre o ensino de primeiras letras na zona rural do interior paulista. Disso resulta a percepção de que o discurso que defendia a igualdade de oportunidades para as populações urbanas e rurais negligenciava, via de regra, a necessidade de promover a igualdade de condições para que a comunidade rural pudesse experienciar as oportunidades que lhes eram prometidas.

The so called Livro de Visitas is a book in which schools inspectors register some general perspectives when visiting a Public School, writing down remarks on the schooling process as, for instance, the results of annual examinations and comments on the school, teachers and students. This paper studies the Livro de visitas of the Rural School Fazenda Ponte Alta/Bela Vista, in Bariri, State of São Paulo. Based on the records of twenty years of activity (1928-1948), some educational elements are highlighted: the demands of the inspectors at that time, how such requirements were (or not) referred by teachers or the community. This allows to sketch a socio-historical scenario focusing on the practices that took place in a school that taught literacy and primary arithmetic. As a result, one can understand that the discourse of equal opportunities between rural and urban schools, so intensely proclaimed by politicians, was not complemented by efforts to guarantee equality of means.
Mémoires d'une école rurale isolée: étude d'un livre de visites (1928-1948)
Memories of a Rural School: a case study based on written documentation (1928-1948)
Keywords: Escola rural; Grupo escolar; Primeiras letras; História da educação; 1928-1948; École rurale; Groupe scolaire; Premières lettres; Histoire de l'éducation; 1928-1948; Rural school; Initial schooling process; History of education; 1928-1948